**Unformatted text preview: **g ( x ) = 1 + p 1 + √ x plugged into f ( x ) = √ x , so applying the chain rule once gives d dx r 1 + q 1 + √ x = 1 2 ± 1 + q 1 + √ x ¶-1 / 2 d dx ± 1 + q 1 + √ x ¶ . Now we need the derivative of p 1 + √ x . Using the chain rule again: d dx q 1 + √ x = 1 2 ( 1 + √ x )-1 / 2 1 2 x-1 / 2 . So the original derivative is d dx r 1 + q 1 + √ x = 1 2 ± 1 + q 1 + √ x ¶-1 / 2 1 2 ( 1 + √ x )-1 / 2 1 2 x-1 / 2 . = 1 8 √ x p 1 + √ x q 1 + p 1 + √ x...

View
Full Document

- Fall '07
- JonathanRogawski
- Math, Calculus, Chain Rule, Derivative, Product Rule, The Chain Rule, dx